Compliant Encryption of JPEG2000 Codestreams - WU, Yongdong (Institutional Knowledge at Singapore Management University, 2004)
This paper presents a compliant encryption method for JPEG 2000 codestreams such that the encryption process does not introduce superfluous JPEG2000 markers in the protected codestream, i.e., the protected codestream preserves the syntax of the original codestream. The proposed encryption method works with any standard ciphers, incurs no storage overhead, introduces negligible computational cost and maintains all the desirable properties of the original JPEG 2000 codestream such as error resilience and scalability.